Criminal Liability For Administering Drugs Causing Acute Kidney Disorders In Children Based On Government Regulation Number 51 Of 2009 Concerning Pharmaceutical Work - Sugiono, Sugiono; Kusno, Kusno; Toni, Toni (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
This study aims to identify and analyze criminal responsibility for administering drugs that cause acute kidney problems in children. As well as knowing and analyzing law enforcement against Pharmaceutical Companies Regarding Contamination of Syrup Drugs. This research is a type of normative research. So that it can be seen that criminal responsibility for administering drugs that result in acute kidney disorders in children must be fully responsible. Especially companies that produce drugs that ultimately cause acute kidney problems in children. In addition, the Food and Drug Supervisory Agency (BPOM) as the drug and food supervisory agency has the right to recommend that law enforcement be carried out against pharmaceutical companies related to drug syrup contamination, strict action must be taken.